Design and Development of a Remote Electric Load Control System Based on the Internet of Things (IoT) for Energy Savings - Ikram Mulky; Mutmainnah; Asyraful Insan Asry (UPPM Poltek ATI Makassar, 2025)
Unsupervised electricity usage can lead to energy waste and increased billing costs. To address this issue, a system capable of effectively monitoring and controlling electrical loads is needed. This study presents the design and development of a remote electrical load monitoring system based on the Internet of Things (IoT) for energy savings, utilizing an ACS712 current sensor, a ZMPT101B voltage sensor, and a relay module as the main components. Load control is carried out via a Telegram application equipped with a cost estimation notification feature as well as overload alerts when the voltage exceeds 250 V or the current surpasses the predefined limit. Testing results show that the measurement accuracy reaches over 94% for voltage and 96% for current, with a total daily energy consumption of five devices amounting to 1.168 kWh and a cost of IDR 1,600.71. This system has proven capable of improving energy efficiency, minimizing waste, and simplifying the process of monitoring and controlling electrical loads.